Study on Household Energy Usage Patterns in Urban and Rural Areas of Nepal - Shahi, Dinesh Kumar; Rijal, Hom Bahadur; Shukuya, Masanori (Journal of the Institute of Engineering, 2020)
In the last decades, the household’s energy demand has increased significantly in various countries including Nepal. In the case of Nepal, 94% of energy use is in the domestic sector. There is a possibility of a huge increase in electricity production, but we are still suffering from load shedding due to the high electricity demand. Electricity use is an important factor for the quality of life and development of a nation. There is not a sufficient number of researches done about electricity consumption in different climatic regions of Nepal which are analyzed by the income level of residents. This study gives descriptive information on the household’s energy uses patterns and investigates the electricity use rate, using electrical appliances in households. This study also identifies the major source of energy use and awareness of energy use. The data were collected from 442 households in three regions in the winter season of 2018. Kalikot is a rural area, Chitwan is a semi-urban, and Kathmandu is an urban area. We have collected electricity bills, family income, and family size, electricity using appliances, expenditure for energy and energy use for heating/cooling, cooking, and lighting. The electricity was used only for lighting purposes in the rural area, but other electrical appliances were used in semi-urban and urban areas. The amount of electricity use has not affected by household income level in the rural area, but it has affected in semi- urban and urban areas. The level of education affects the use of the LED significantly. This study would be helpful to know the electricity use patterns which is useful for energy saving and energy management of the rural and urban areas of Nepal.